Regulating the Coordination Geometry and Oxidation State of Single‐Atom Fe Sites for Enhanced Oxygen Reduction Electrocatalysis - Wang, Minjie; Wang, Li; Li, Qingbin; Wang, Dan; Yang, Liu; Han, Yongjun; Ren, Yuan; Tian, Gang; Zheng, Xiaoyang; Ji, Muwei; Zhu, Caizhen; Peng, Lishan; et al. (Small (Weinheim an der Bergstrasse, Germany), 2023)
FeNC catalysts demonstrate remarkable activity and stability for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells and Zn–air batteries (ZABs). The local coordination of Fe single atoms in FeNC catalysts strongly impacts ORR activity. Herein, FeNC catalysts containing Fe single atoms sites with FeN3, FeN4, and FeN5 coordinations are synthesized by carbonization of Fe‐rich polypyrrole precursors. The FeN5 sites possess a higher Fe oxidation state (+2.62) than the FeN3 (+2.23) and FeN4 (+2.47) sites, and higher ORR activity. Density functional theory calculations verify that the FeN5 coordination optimizes the adsorption and desorption of ORR intermediates, dramatically lowering the energy barrier for OH− desorption in the rate‐limiting ORR step. A primary ZAB constructed using the FeNC catalyst with FeN5 sites demonstrates state‐of‐the‐art performance (an open circuit potential of 1.629 V, power density of 159 mW cm−2). Results confirm an intimate structure‐activity relationship between Fe coordination, Fe oxidation state, and ORR activity in FeNC catalysts. FeNC catalysts with different Fe single‐atom coordination geometries (FeN3, FeN4, or FeN5) are synthesized by pyrolysis of Fe‐polypyrrole precursors. FeN5 sites offer the highest Fe oxidation state (+2.62), strongest Fe–N interaction, lowest energy barrier for OH− desorption, and highest intrinsic activity for oxygen reduction reaction in alkaline media.